Nausicaä of the Valley of the Wind [videorecording (DVD)] - Miyazaki, Hayao, 1941- (Shout! Factory, 2017)
Set far in the future on a dying earth, princess Nausicaä of the Valley of the Wind attempts to create peace between her father's kingdom and another fighting for natural resources.